CEFR updates (2020)-based next-gen immersive learning in 5 steps - DEMİRDÖVEN, Gökhan Haldun (Frontiers in Education, 2025)
The Common European Framework of Reference for Languages (CEFR) can be defined as an action-oriented framework that systematically employs “can do” descriptors to structure the processes of foreign language teaching and learning. After a comprehensive literature review, it was evident that there was no descriptive content analysis study on the CEFR (2020) in terms of immersive learning technologies. Based on the existing shortcomings, the focus of this study was to identify the updates in the CEFR and the key elements that formed the connection points of immersive learning. This study, due to its scope and content, was conducted within the framework of qualitative research methodologies, employing document analysis and descriptive content analysis. Based on the research results, it is possible to assert that the situational teaching method based on the digital/human digital twins; cognitive immersive language learning (CILL) approach rooted cognitive immersive rooms; interactive conversational agents capable of code switching; adaptive gamification approaches combining gamification techniques and educational data mining methods, accent-robuts automated speech recognition systems grounded in the sociolinguistic approach, and online socialization metaverse networks woven with social virtual reality (SVR) and collaborative virtual environment (CVE) concepts built upon the phenomenon of heterotopia stood out as the “paradigm identifiers” for the next-gen of foreign language teaching forms. As far as the research implications are concerned, the results affirmed the components and pedagogical approaches that would form the backbone for the integration of immersive technologies into CEFR-based language learning. Theoretically speaking, the CEFR-based immersive learning method was proposed for future studies in the age of AI-driven technologies.